Impact of social media on academic performance and interpersonal relation: A cross-sectional study among students at a tertiary medical center in East India - Sandeep Lahiry; Shouvik Choudhury; Suparna Chatterjee; Avijit Hazra (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: There is limited evidence on the influence of social media among medical students. AIMS: To assess the pattern of social media usage among medical students in eastern part of India and analyze self-perceived impact on academic performance and interpersonal relations. Methods: This cross-sectional study was based on an online survey, taken by 650 medical students at a tertiary medical center in Kolkata. The survey was created using an online tool, Google Forms. It assessed social media usage patterns and students' perspective on how it affects their academic performance and interpersonal relations. STATISTICAL ANALYSIS USED: Pearson's correlation coefficient was used to quantify the association between self-rated academic performance and social and physical well-being, with different variables, assuming linear relationships. P <0.05 was considered statistically significant. RESULTS: The usable responder rate was 55.23%, with majority being undergraduates (57.3%) in the age group of 18-24 years. The proportion who confirmed using social media was 88.58% (95% confidence interval [CI]: 85.29%-91.87%), mainly for academic purposes (82.73%; 95% CI: 78.82%-86.64%). In general, social media usage was more prevalent among medical students compared to paramedical and nursing students (P = 0.009), although the extent of use for an academic purpose was comparable. Nearly two-thirds (60.87%) regarded social networking having a positive (improved) impact on academic performance. However, the perceived impact on interpersonal relations was inconclusive (i.e., was positive and negative in a nearly equal measure; 45% each). CONCLUSIONS: Social media usage for academic purposes is high among medical and paramedical students. Students benefit from social networking and are conscious of its positive as well as negative influence on interpersonal relations.